Existence of Solutions for Fourth-Order Four-Point Boundary Value Problem on Time Scales. (19th August 2009) - Yang, Dandan; Li, Gang; Bai, Chuanzhi
Abstract : We present an existence result for fourth-order four-point boundary value problem on time scales. Our analysis is based on a fixed point theorem due to Krasnoselskii and Zabreiko.